2011
DOI: 10.1111/j.1365-2788.2011.01451.x
|View full text |Cite
|
Sign up to set email alerts
|

Development and behaviour in Marshall-Smith syndrome: an exploratory study of cognition, phenotype and autism

Abstract: Systematic collection of developmental and behavioural data in very rare entities such as MSS allows recognition of specific patterns in these qualities. Clinical recognition of physical,developmental and behavioural features is important not only for diagnosis, prognosis and counselling of families, but also increases our understanding of the biological basis of the human physical and behavioural phenotype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 59 publications
1
32
1
Order By: Relevance
“…We have previously assessed cognition, behavioural phenotype, and autism in Marshall-Smith syndrome (MSS), a very rare entity characterized by failure to thrive, developmental delay, abnormal bone maturation, and a characteristic face. In comparison with the MSS study with a similar methodology, 17 the findings in the present study indicate that in classic PTHS the behavioural phenotype is clearly similar to behaviours seen in ASD. This can be noted not only in the difficulties in engaging and communicating with others, but also in the much higher occurrence and level of severity of repetitive motor stereotypies, repetitive play and fascination with specific objects, and difficulties with changes in daily activities or routines.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…We have previously assessed cognition, behavioural phenotype, and autism in Marshall-Smith syndrome (MSS), a very rare entity characterized by failure to thrive, developmental delay, abnormal bone maturation, and a characteristic face. In comparison with the MSS study with a similar methodology, 17 the findings in the present study indicate that in classic PTHS the behavioural phenotype is clearly similar to behaviours seen in ASD. This can be noted not only in the difficulties in engaging and communicating with others, but also in the much higher occurrence and level of severity of repetitive motor stereotypies, repetitive play and fascination with specific objects, and difficulties with changes in daily activities or routines.…”
Section: Discussionsupporting
confidence: 66%
“…The child psychiatrist is experienced in assessing individuals with autism and other developmental disabilities. 3,17 In-person interviews with parents were used to assess past and current development, and functioning for the domains communication, (adaptive) behaviour, and social-emotional development. Parents were invited to provide further information through a standardized questionnaire assessing emotional and behavioural problems.…”
Section: Test Instrumentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both of these conditions are characterised by overgrowth, musculoskeletal abnormalities, abnormal behaviour including autistic traits, and mild to moderate learning difficulties. Magnetic resonance imaging analyses have shown that these individuals recapitulate some of the gross defects observed in the homozygous Nfix knockout mouse, including hypoplasia of the corpus callosum and ventricular dilation [42], [43]. Although no gross defects in hippocampal morphology were reported in these studies, our results suggest that individuals with these disorders may exhibit subtle defects in hippocampal morphology and hippocampal-dependent behaviour, and that this could contribute to their neurological deficits.…”
Section: Discussionmentioning
confidence: 49%
“…Osteopenia, nontraumatic fractures, and other bony and connective tissue findings have been described during childhood (Flatz and Natzschka, 1978;Adam et al, 2005). Cryptorchidism, anteriorly placed anus, hypospadias, vesicoureteral reflux, pyloric stenosis, gingival hypertrophy, Wilms tumor, IgA deficiency, pigmentary skin defects (Passalacqua et al, 2011), hypoplasia of the labia majora, labia minora, and clitoral hood (Diab et al, 2003), and developmental and behavioral alterations have been reported previously (Van Balkom et al, 2011), but there has been no description of hypertrophic labia minora and clitoris as in this current patient. The frequent and significant respiratory difficulties in MSS result from a combination of pathologies, which mainly comprise upper airway obstruction (retrognathia, choanal stenosis, abnormal larynx, and laryngomalacia) and aspiration pneumonia.…”
Section: Discussionmentioning
confidence: 89%